1988
DOI: 10.1007/bf01618106
|View full text |Cite
|
Sign up to set email alerts
|

Automated charting of physiological variables in anesthesia: A quantitative comparison of automated versus handwritten anesthesia records

Abstract: Eight physiological variables--tidal volume, breathing rate, end-tidal carbon dioxide fraction, oxygen fraction in the anesthetic circuit, oxygen saturation by pulse oximetry, systolic and diastolic blood pressure, and heart rate--recorded on-line by a commercially available automated system were compared with the same variables recorded on handwritten anesthesia records. We quantified the differences between the automated and handwritten records generated from the same 30 patients (2,412 minutes of general an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0
1

Year Published

1992
1992
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(36 citation statements)
references
References 8 publications
1
34
0
1
Order By: Relevance
“…3 This was illustrated in the study by Lerou et al who reported error fractions four times larger for systolic BP, HR and SpO 2 during induction and at the end of the procedure than in the maintenance phase. 9 Another reason may be due to artifacts that are common in the monitoring of physiological variables. 6,s,9 Since their presence is rare in the hand recorded anesthetic record, it is likely that it has become accepted practice for the anesthetist to adjust or eliminate these errors when charting physiological variables.…”
Section: Discussionmentioning
confidence: 99%
“…3 This was illustrated in the study by Lerou et al who reported error fractions four times larger for systolic BP, HR and SpO 2 during induction and at the end of the procedure than in the maintenance phase. 9 Another reason may be due to artifacts that are common in the monitoring of physiological variables. 6,s,9 Since their presence is rare in the hand recorded anesthetic record, it is likely that it has become accepted practice for the anesthetist to adjust or eliminate these errors when charting physiological variables.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10] These studies predominantly relate to the accuracy of physiological data. In a recent study, completion rates were assessed for six text entry fields on AIMS records, 24 and results showed rates similar to those seen in this study; however, randomized evaluations directly comparing the completeness of text entry data between different methods of recordkeeping are lacking.…”
Section: Discussionmentioning
confidence: 99%
“…6,21 Several studies have compared the accuracy and completeness of physiologic data in handwritten and AIMS records and have found AIMS records to be superior. [7][8][9][10] This is not surprising, as electronic data from physiologic monitors lend themselves to automated capture by an AIMS. It is less clear whether AIMS technology facilitates recording information that can be obtained only by clinical observation.…”
Section: Résumémentioning
confidence: 97%
See 1 more Smart Citation
“…Lerou et al evaluated automated charting using the Ohmeda Modulus II TM Anesthesia System vs handwritten records by comparing the acquisition of eight physiological variables in 30 elective eye surgeries. 37 Two records were compared for each patient, the handwritten record and that recorded by AARK. Anesthesiologists had two advantages; there was a centralized unit that displayed all eight variables on one screen, and they knew beforehand that their handwritten records would be compared with the automated record.…”
Section: Anesthesia Information Management Systems (Aims)mentioning
confidence: 99%